ROXIFYonline: Helping Students Improve Their Writing through Online Feedback - Roxanne Miller; George Miller (Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
Today’s students want immediate feedback on their writing which instructors often cannot provide. They embrace the internet and want to use it for learning. To keep pace with these desires, Roxifyonline was created. It is a new online Computer Assisted Language Learning (CALL) tool that provides automated essay feedback for use by students worldwide. The program was originally written for ESL learners in Hong Kong, but is now being used by students throughout the Asia Pacific region and in Finland. It is based on both empirical research and that of other academics. The program is robust enough to be used for general academic writing from upper secondary through post graduate levels. It is a free Independent Learning (IL) tool. The program utilizes vocabulary to identify possible errors and provides online IL links to aid in the correction of possible errors in writing. Unlike other programs, it does not provide suggested corrections. This can help students to become more autonomous in their learning. Comparisons can be made between drafts, and there is an annotation function which can allow for more individualized peer and teacher feedback.